Vertical-cavity surface-emitting lasers with integrated refractive microlenses - Peters, F. H., author; Robinson, G., author; Carson, R. F., author; Schneider, R. P., author; Lear, Kevin L., author; Du, T. C., author; Warren, M. E., author; Kilcoyne, S. P., author; Blum, O., author; IEE, publisher (Colorado State University. Libraries, 1995)
The fabrication and performance of a vertical cavity surface emitting laser array integrated with microlenses are reported. The lasers emit at 967nm through the substrate with integral polyimide microlenses. This design reduces beam divergence and provides an integrated device that emits a nearly collimated beam for applications such as optical interconnects.
Keywords: vertical cavity surface emitting lasers; optical polymers; lasers